Building Performance - Narafu, Tatsuo (World Bank, Washington, DC, 2013)
The strong main shock of the Great East Japan Earthquake (GEJE) of March 11, 2011, caused little damage to buildings. Buildings designed under the current building code and those with base isolation fared well. However, seismic design guidelines for nonstructural members had not been considered adequately, which resulted in problems such as the collapse of ceiling panels. Soil liquefaction occurred in reclaimed coastal area along Tokyo Bay and riverside areas. The key lessons of the GEJE are that seismic-resistant building design prevent collapse of buildings and protects human lives, that retrofitting vulnerable buildings is essential to reduce damage, that seismic isolation functioned well, and that nonstructural building components can cause serious damage. When applying these lessons to developing countries, local technical and socioeconomic conditions should be taken into account. This report gives findings; lessons; and recommendations for developing countries.